Study on the mechanism of the repeated asphalt ageing and recycling based on the macro-performance. Issue 4 (1st October 2016) - Zhang, Haitao; Liu, Hongwei; Zhang, Zhende
Abstract : The basic theory about the repeated asphalt ageing and recycling has been less researched in the recycling asphalt pavement, but mainly focused on the once asphalt ageing and recycling. In the project, the ageing asphalt specimens with the different ageing time (5, 20 and 70 hours) have been finished by using AH-90# asphalt (25°C penetration is 80–100/0.1 mm) at 163°C. The tests of the repeated asphalt ageing and recycling have been conducted through the material combinations among the ageing asphalt specimens and the new asphalt and recycling agent. The objective is to discuss the performance and mechanism of the repeated asphalt ageing and recycling. The research contents include: the determination of the state and colloidal structure of the ageing asphalt, the selection of the new asphalt and recycling agent, and the test and mechanism of the repeated asphalt ageing and recycling. By the analysis on the test data, the state and the colloidal structure of the ageing asphalt has been determined based on the ageing index, the performance and its changing law of the repeated asphalt ageing and recycling have been evaluated based on the asphalt macro-performance indices. On the basis of it, the three stages about the performance change of the repeated asphalt ageing and recycling have been put forward, and the problem of the existing theory about the ageing asphalt has been pointed out, and the non-unilateral changes of the performance of the repeated asphalt ageing and recycling have been demonstrated.